"Still on the Fence": A Mixed Methods Investigation of COVID-19 Vaccine Confidence Among Health Care Providers. (June 2022) - Choi, Kristen; Chang, John; Luo, Yi X.; Lewin, Bruno; Munoz-Plaza, Corrine; Bronstein, David; Rondinelli, June; Bruxvoort, Katia
Background: There is evidence of disparities in COVID-19 vaccine acceptance among health care providers. The purpose of this study was to examine confidence receiving and recommending COVID-19 vaccines by health care provider type and race/ethnicity. Methods: This mixed methods study involved a cross-sectional survey and qualitative, semi-structured interviews from March to May 2021 among a sample of physicians, advanced practice providers, nurses, and pharmacists. These workers were recruited through voluntary response sampling from an integrated health system in Southern California. The primary dependent variables were (a) confidence in vaccine safety, (b) confidence in vaccine effectiveness, and (c) intent to recommend the vaccine to others. The primary independent variables were health care provider type and race/ethnicity. Findings: A total of 2, 948 providers completed the survey. Nurses relative to physicians were 15% less likely to perceive the COVID-19 vaccine to be safe (risk ratio [RR] = 0.85; 95% confidence interval [CI] = 0.83–0.87); 27% less likely to perceive the vaccine to prevent COVID-19 (RR = 0.73; 95% CI = 0.69–0.76); and 11% less likely to recommend the vaccine to others (RR = 0.89; 95% CI = 0.87–0.91). Hispanic/Latinx providers were 10% less likely to perceive the vaccine to prevent COVID-19 (RR = 0.90; 95% CI = 0.83–0.98) relative to White providers. Qualitative themes included: No need for vaccine; distrusting vaccine research and roll-out; caretaking barriers; uncertainty and potential to change one's mind; framing vaccine decisions around personal beliefs. Conclusions & Application to Practice: Health care workplaces should consider interventions to increase COVID-19 vaccination among their workers, including education and mandatory vaccination policies.